Home-grown ICT solutions in agriculture come from young entrepreneurs - Baumüller, Heike; Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2016)
Young innovators in Africa, the Caribbean, and Pacific region, have recognised the need for creative solutions to raise agricultural productivity and the huge prospective market for their ICT-enabled services in agriculture. Although they still face many challenges, their products have the potential to transform agricultural value chains in developing countries.